(untitled) (Bangladesh Journal of Zoology, 2021)
This investigation was undertaken to evaluate some physico-chemical parameter of water of the trans-boundary Haora River in Brahmanbaria during October 2018 to September 2019 from three different sites. The study revealed that air temperature at three different sites ranged 13 – 38 °C while the water temperature was 11 – 32 °C. Transparency of water varied from 18 – 55 cm Secchi depth and became more turbid during monsoon. The average values of pH and dissolved oxygen (DO) both in sites and seasons were within the standard limits for aquatic organisms. Total dissolved solids (TDS) were found between 77 and 352 mg/L and varied greatly in seasons. Electric conductivity (EC) was ranged 135 to 650 μS/cm. On the other hand, maximum and minimum hardness of water were recorded as 322 mg/L and 118 mg/L respectively and become lowest in monsoon. The rainy season bear high torrential water which brought huge amount of different types of garbage through the water flow from the Indian part. Most of the garbage are of floating and submerged type as plastic containers, bottles, polybags, cans, etc along with natural debris. During the study period highest (172 kg) and lowest (113 kg) plastic garbage were collected in May and July respectively. This foreign garbage may impair the normal healthiness of the river ecology. Bangladesh J. Zool. 49(1): 137-146, 2021